To solve the quadratic equation \(3x^2 + 18x + 24 = 0\) using the Quadratic Formula, we first identify the coefficients \(a\), \(b\), and \(c\) in the standard form \(ax^2 + bx + c = 0\):
- \(a = 3\)
- \(b = 18\)
- \(c = 24\)
The Quadratic Formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Now, we can substitute the values of \(a\), \(b\), and \(c\) into the formula:
-
Calculate the discriminant (\(b^2 - 4ac\)): \[ b^2 - 4ac = 18^2 - 4 \cdot 3 \cdot 24 \] \[ = 324 - 288 \] \[ = 36 \]
-
Substitute the values into the quadratic formula: \[ x = \frac{-18 \pm \sqrt{36}}{2 \cdot 3} \] \[ = \frac{-18 \pm 6}{6} \]
-
Calculate the two possible solutions:
- First solution: \[ x = \frac{-18 + 6}{6} = \frac{-12}{6} = -2 \]
- Second solution: \[ x = \frac{-18 - 6}{6} = \frac{-24}{6} = -4 \]
Thus, the solutions to the equation \(3x^2 + 18x + 24 = 0\) are:
\[ x = -2 \quad \text{and} \quad x = -4 \]
The correct response is:
x=−2, x=−4.